2012
DOI: 10.1117/12.909161
|View full text |Cite
|
Sign up to set email alerts
|

Photoacoustic characterization of radiofrequency ablation lesions

Abstract: Radiofrequency ablation (RFA) procedures are used to destroy abnormal electrical pathways in the heart that can cause cardiac arrhythmias. Current methods relying on fluoroscopy, echocardiography and electrical conduction mapping are unable to accurately assess ablation lesion size. In an effort to better visualize RFA lesions, photoacoustic (PA) and ultrasonic (US) imaging were utilized to obtain co-registered images of ablated porcine cardiac tissue. The left ventricular free wall of fresh (i.e., never froze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…These local transients can be imaged using a traditional US transducer (2022), providing an optical absorption map with resolutions on the order of tens of micrometers (or hundreds of micrometers using a 7.5 MHz US probe, which is common for EP intracardiac or transesophageal US applications and comparable to MRI) and at imaging depths in excess of a centimeter (1822). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These local transients can be imaged using a traditional US transducer (2022), providing an optical absorption map with resolutions on the order of tens of micrometers (or hundreds of micrometers using a 7.5 MHz US probe, which is common for EP intracardiac or transesophageal US applications and comparable to MRI) and at imaging depths in excess of a centimeter (1822). …”
Section: Introductionmentioning
confidence: 99%
“…Due to the wavelength dependence of μ abs , spectroscopic photoacoustic imaging (sPA) can be performed for tissue characterization purposes (2325). PA imaging's reliance upon ultrasonic sensing allows straightforward co-registration with anatomical US images, providing molecularly sensitive anatomical PA/US images (2022). For these reasons, PA imaging is being pursued as a powerful medical imaging modality in cancer detection (26), disease staging (22) and therapy monitoring (21).…”
Section: Introductionmentioning
confidence: 99%
“…As examples, real-time OA imaging during radiofrequency (RF) ablation of ex vivo tissues has being shown 26 . Validation of the OA images of RF ablated tissues was further showcased 27 . Additionally, OA has been used to monitor ultrasound heating 28 , laser thermal treatments 21,29 or cryoablation 30 .…”
Section: Introductionmentioning
confidence: 99%
“…Photoacoustic imaging has multiple medical applications, with one focus being its potential to guide a variety of surgeries and procedures, including neurosurgeries [23], spinal fusion surgeries [24], hysterectomies [25]- [27], prostatectomies [28], fetal surgeries [29], abdominal surgeries [30], minimally invasive robotic surgeries [26], [31], and liver biopsies [32], [33]. In addition, photoacoustic imaging has been used to distinguish between ablated and healthy myocardial tissue after a radiofrequency ablation [34]- [36]. Bouchard et al [34] demonstrated 6-10 dB of contrast between ablated regions and normal tissue using a wavelength of 750 nm in ex vivo porcine cardiac tissue but with limited penetration depth.…”
Section: Introductionmentioning
confidence: 99%